30–50 GHz high‐gain CMOS UWB LNA. Issue 25 (1st December 2013) - Yang, Ge Liang; Liu, Faen; Muhammad, Amin; Wang, Zhigong
Abstract : A 30–50 GHz CMOS ultra‐wideband (UWB) low‐noise amplifier (LNA) with a flat high power gain ( S 21 ), along with a flat low‐noise figure (NF) is demonstrated for the Atacama large millimetre array (ALMA) band‐1 (31.3–45 GHz) system applications. The high S 21 and low NF are achieved because the triple‐well transistors are utilised with their respective source and body terminals connected together. Furthermore, the bandwidth extension and gain flatness is achieved due to the careful design of the inductive‐peaking networks. The LNA has a measured S 21 of 21.5 ± 1.5 dB, a minimum NF (NFmin ) of 3.8 dB at 32.5 GHz, an average NF (NFavg ) of 4.67 dB over the range of 30–50 GHz and an input third‐order intercept point (IIP3) of 0 dBm, with a DC power consumption of 20.4 mW at 1.2 V supply. The proposed LNA outperforms all the reported commercial standard CMOS Q ‐band LNAs, with the highest gain bandwidth product and highest IIP3 suitable for the ALMA band‐1 system applications.